2016
DOI: 10.1002/lom3.10100
|View full text |Cite
|
Sign up to set email alerts
|

A standard protocol for NaBH4reduction of CDOM and HS

Abstract: Sodium borohydride (NaBH 4 ) selectively reduces ketones/aldehydes to alcohols and quinones to hydroquinones and has been used to reduce these carbonyl moieties within humic substances (HS) and chromophoric dissolved organic matter (CDOM) to gain insight into their contributions to the optical/photochemical properties of these materials. To further investigate the effects of borohydride reduction on the absorption and emission properties of HS and to develop a standard protocol for this reduction, the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(78 citation statements)
references
References 27 publications
12
66
0
Order By: Relevance
“…No changes in optical properties were observed, suggesting that our Sargassum SPE-DOM samples could not undergo further oxidation. Reduction of Sargassum SPE-DOM samples was performed using NaBH 4 following methods and recommendations reported previously (Schendorf et al, 2016). Briefly, SPE-DOM samples were adjusted to pH 10-11 and were reduced using a 25 times mass excess (based on the DOC concentration of the SPE-DOM sample) aliquot of NaBH 4 .…”
Section: Titrations and Reductions Of Sargassum Spe-dommentioning
confidence: 99%
“…No changes in optical properties were observed, suggesting that our Sargassum SPE-DOM samples could not undergo further oxidation. Reduction of Sargassum SPE-DOM samples was performed using NaBH 4 following methods and recommendations reported previously (Schendorf et al, 2016). Briefly, SPE-DOM samples were adjusted to pH 10-11 and were reduced using a 25 times mass excess (based on the DOC concentration of the SPE-DOM sample) aliquot of NaBH 4 .…”
Section: Titrations and Reductions Of Sargassum Spe-dommentioning
confidence: 99%
“…44,45 However, verifying this assumption is difficult for datasets containing environmental samples. While multiple studies have questioned the superposition assumption due to electronic interactions between chromophores, [46][47][48][49] evidence of electronic interactions have mainly been observed under conditions of strong chemical oxidation, 50 although one study reported selfquenching of humic acid in HPSEC separations. 51 The extent to which electronic interactions undermine the use of PARAFAC under environmental conditions is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf leachates were adjusted to pH 7 and pH 10 using high purity NaOH (Fisher, Hampton, NH, USA), and the optical properties were recorded for each pH. A total of 17.0 mg of sodium borohydride (Acros Organics, Hampton, NH, USA) was added to 17.0 mL of leaf tea, and the reactions were allowed to proceed for 48 h [16]. Leachates were then filtered through 0.45 µm nylon filters and optical properties were again recorded at pH 10, pH 7 and natural pH.…”
Section: Borohydride Treatmentsmentioning
confidence: 99%
“…Additions of HClO 4 were used to adjust pH (VWR). Results are reported at a neutral pH of 7, as recommended by [16]. All experiments were run with three analytical replicates.…”
Section: Borohydride Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation